2016
DOI: 10.1111/tmi.12790
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic cryptococcal antigen prevalence detected by lateral flow assay in hospitalised HIV‐infected patients in São Paulo, Brazil

Abstract: 3.1% of HIV-infected inpatients with CD4 <200 cells/μl without symptomatic meningitis had cryptococcal antigenemia in São Paulo, suggesting that routine CRAG screening may be beneficial in similar settings in South America. Our study reveals another targeted population for CRAG screening: hospitalised HIV-infected patients with CD4 <200 cells/μl, regardless of ART status. Whole blood CRAG LFA screening seems to be a simple strategy to prevention of symptomatic meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 13 publications
3
38
2
3
Order By: Relevance
“…Our experience show a high LP acceptance once detailed information was given on its risks and benefits of LP. We also observed cryptococcal meningitis individuals had higher CrAg titers >1:160 as compared with CrAgpositive individuals with no CSF involvement (43% vs 18%) as expected [10,17,[29][30][31].…”
Section: A C C E P T E Dsupporting
confidence: 80%
“…Our experience show a high LP acceptance once detailed information was given on its risks and benefits of LP. We also observed cryptococcal meningitis individuals had higher CrAg titers >1:160 as compared with CrAgpositive individuals with no CSF involvement (43% vs 18%) as expected [10,17,[29][30][31].…”
Section: A C C E P T E Dsupporting
confidence: 80%
“…This study found a CrAg-positive prevalence of 3.1%, but did not perform LP to exclude isolated antigenemia. 16 The present study recruiting only inpatients found 4.8% Regarding baseline characteristics, we did not find difference in CD4 cell count between CrAg-positive and CrAg-negative patients (29 × 56 cells/mm 3 ), like the Vietnam group, 14 but we found statistic difference between those with or without cryptococcal meningitis.…”
Section: Discussioncontrasting
confidence: 63%
“…Another Brazilian study conducted in state of Sao Paulo, Southeast Region, analysed HIV‐infected asymptomatic outpatients, with CD4 counts <200 cells/mm 3 . This study found a CrAg‐positive prevalence of 3.1%, but did not perform LP to exclude isolated antigenemia . The present study recruiting only inpatients found 4.8% (4/83) of isolated antigenemia after excluding cases of meningitis and fungemia by lumber puncture and blood culture.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In other African and American studies, it was also found in HIV/AIDS patients with CD4 + T cell lymphocyte count between 100-200 cells/µl. 5,6 This study aim to determine the proportion of Cryptococcal antigenemia in HIV/AIDS patients treated at Dr. Soetomo Hospital Surabaya.…”
Section: Kata Kunci: Cryptococcal Antigenemia Aids Hiv Rsud Dr Somentioning
confidence: 99%